2014
DOI: 10.5121/ijcses.2014.5301
|View full text |Cite
|
Sign up to set email alerts
|

Process and Product Quality Assurance Measures in CMMI

Abstract: Process and product quality assurance are very important aspects in development of software. Process and product quality assurance monitor the software engineering processes and methods to ensure quality. It is the process of confirming and verifying that whether services and products meet the customer expectation or not. This research will identify general measures for the specific goals and its specific practices of Process and Product Quality Assurance Process Area in Capability Maturity Model Integration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Observations made establish that many limitations on Quality Assurance enhance the success of some particular e-health programs or projects. A study on quality assurance found that it increases the probability and success of technological projects like Software Engineering through an adequate level of instilled confidence and satisfaction of required Quality ( Khraiwesh, 2014).…”
Section: Independent Variablementioning
confidence: 99%
“…Observations made establish that many limitations on Quality Assurance enhance the success of some particular e-health programs or projects. A study on quality assurance found that it increases the probability and success of technological projects like Software Engineering through an adequate level of instilled confidence and satisfaction of required Quality ( Khraiwesh, 2014).…”
Section: Independent Variablementioning
confidence: 99%
“…Various researches aimed to measure the software process that has been suggested, such as [21,[31][32][33][34][35][36][37][38][39][40][41]. The works that are related the most to our work are represented in the works of [21,31,32,[35][36][37][38][39][40][41]. Baumertand McWhinney [42] point out to several observations that are usefulfor measuring the practices (general characteristics) that are defined in the Capability Maturity Model for CMM/SW.…”
Section: The Relevant Workmentioning
confidence: 99%
“…Loconsole [13] (CMM/SW), rather than (CMMI/SW). Khraiwesh, [31,[35][36][37][38][39]41] identifies a set of measures for processessuch as validation, process and product quality assurance, risk management, project planning, project monitoring and control, and configuration management in CMMI/SW.…”
Section: The Relevant Workmentioning
confidence: 99%
“…Artinya penjaminan mutu internal yaitu meningkatkan lingkungan internal dan proses sedemikian rupa sehingga efektivitas pembelajaran dan pengajaran dapat dipastikan untuk mencapai tujuan yang direncanakan. Khraiwesh (2014) menyatakan "quality assurance are process driven approaches with specific steps to achieve development goals" yakni sebuah proses jaminan kualitas produk melalui pendekatan dengan langkah-langkah khusus untuk mencapai tujuan pengembangan. Sistem penjaminan mutu pendidikan adalah proses yang mencakup seluruh aspek penyelenggaraan pendidikan dengan memanfaatkan berbagai sumberdaya untuk mencapai SNP.…”
Section: St National Seminar On Elementary Education (Snpd 2018)unclassified